Influence of antimicrobial photodynamic therapy on the bond strength of endodontic sealers to intraradicular dentin: A systematic review and meta-analysis - Banci, Henrique Augusto [UNESP]; Strazzi-Sahyon, Henrico Badaoui [UNESP]; Bento, Victor Augusto Alves [UNESP]; Sayeg, João Mateus Cavalaro [UNESP]; Bachega, Mariana de Oliveira [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Araújo, Gustavo Sivieri de [UNESP] (Elsevier, 2023)
Background: The objective of this systematic review and meta-analysis (SRMA) was to investigate the influence of antimicrobial photodynamic therapy (aPDT) on the bond strength of endodontic sealers to intraradicular dentin. Methods: This SRMA followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and was registered in the International Prospective Registry of Systematic Reviews (PROSPERO) (CRD42022319856). A population, intervention, control, and outcome (PICO) question was formulated: “Does antimicrobial photodynamic therapy decrease the bond strength of root canal sealers?”. A literature search was performed in PubMed/MEDLINE, Embase, Web of Science, Scopus, Cochrane Library, and ProQuest databases until July 2022. Joanna Briggs Institute Critical Assessment Guidelines for Quasi-Experimental Studies were used for quality assessment. The meta-analysis was based on the inverse variance (IV) method (p<0.05). Results: Out of an initial 345 articles, 8 in vitro studies were included, published between 2013 and 2022. The studies were qualitatively analyzed; two studies showed a positive effect, two studies a negative effect, and the other studies showed no effect on bond strength of endodontic sealers to intraradicular dentin. Seven of the studies were included in the SRMA, which indicated that there was no significant difference in bond strength when using aPDT (P = 0.90; MD: -0.03; 95% CI: -0.46 to -0.41). There was a high level of evidence for each meta-analysis outcome. Conclusion: It can be concluded that the use of aPDT as a method of root canal disinfection does not negatively influence the bond strength of endodontic sealers in the root canal.
Keywords: Bond strength; Endodontic sealers; Meta-analysis; Photodynamic therapy; Root canal treatment; Systematic review